“I’M A SUPERHERO”: INCREASING STUDENTS’ PSYCHOLOGICAL CAPITAL THROUGH STORYTELLING - Unika Prihatsanti; Ika Zenita Ratnaningsih; Anggun Resdasari Prasetyo (LPMPP Universitas Negeri Yogyakarta, 2020)
Psychological capital as a positive psychological characteristic that reflected through several components such self-efficacy, hope, optimism, and resilience is important to adjust the changes that experienced by freshmen in a college. Storytelling is a form of communication that allows the listener to fully immerse in the content of the story and experience the emotions felt by the characters. This study aims to determine the effect of storytelling activities use “I’m a Superhero” module to increase students’ psychological capital. Quasi-experimental methods were used in the study that involving 127 first-year college students. The subjects of this study divided into two groups, 56 for the experimental group and 71 for the control group. The interventions were done for 22 days divided into six sessions and described in